BUDIDAYA JAMUR PERUSAK KAYU III. BUDIDAYA AURICULARIA POLYTRICA PADA DOLOK LIMA JENIS KAYU - Sihati Suprapti (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
Ear mushroom (Auricularia polytrica) was cultivated on logs of five wood species, i.e. hamerang (Ficus grossularoides Burn.f.), jeungjing (Albizia falcataria (L.) Fosb.), jirak (Symplocos fasciculata Zoll.), kihuut (Vernonia arborea Ham.) and manii (Maesopsis eminii Engl.). The logs were kept slanted on an angle of ± 60° with bamboo supports in a 1.5 m by 2 m room roofed with bamboo plait, at Bogor. The mature mushroom was harvested daily after the growth of the fruiting body.The logs start producing fungus two months after inoculation. The highest harvest was obtained at fourth month of observation. The average yield per month per m3 of log was obtained from kihuut (15.69 kg), jeungjing (10.76 kg), manii (9,46 kg), hamerang (8.59 kg) and jirak (1.29 kg).After seven month observation, an average yield of 1.05 kg log (kihuut), 0. 725 kg (jeungjing), 0.556 kg (manii), 0.349 kg (hamerang], and 0.125 kg (jirak) were obtained. Relative high total yield of ear mushroom during the seven month observation was obtained from kihuut (109.84 kg), jeungjing (75.285 kg), manii (66.202 kg), hamerang (60.103 kg) and the lowest total yield was on jirak (9.036 kg) per m3 of log.